Characterization of HIV-1 Epidemic in Kyrgyzstan - Sivay, Mariya V.; Totmenin, Alexei V.; Zyryanova, Daria P.; Osipova, Irina P.; Nalimova, Tatyana M.; Gashnikova, Mariya P.; Ivlev, Vladimir V.; Meshkov, Ivan O.; Chokmorova, Umut Z.; Narmatova, Elmira; Motorov, Ulukbek; Akmatova, Zhyldyz; et al. (Frontiers in Microbiology, 2021)
Kyrgyzstan has one of the highest rates of HIV-1 spread in Central Asia. In this study, we used molecular–epidemiological approaches to examine the HIV-1 epidemic in Kyrgyzstan. Samples were obtained from HIV-positive individuals who visited HIV/AIDS clinics. Partial pol gene sequences were used to identify HIV-1 subtypes and drug resistance mutations (DRMs) and to perform phylogenetic analysis. Genetic diversity and history reconstruction of the major HIV-1 subtypes were explored using BEAST. This study includes an analysis of 555 HIV-positive individuals. The study population was equally represented by men and women aged 1–72 years. Heterosexual transmission was the most frequent, followed by nosocomial infection. Men were more likely to acquire HIV-1 during injection drug use and while getting clinical services, while women were more likely to be infected through sexual contacts (p < 0.01). Heterosexual transmission was the more prevalent among individuals 25–49 years old; individuals over 49 years old were more likely to be persons who inject drugs (PWID). The major HIV-1 variants were CRF02_AG, CRF63_02A, and sub-subtype A6. Major DRMs were detected in 26.9% of the study individuals; 62.2% of those had DRMs to at least two antiretroviral (ARV) drug classes. Phylogenetic analysis revealed a well-defined structure of CRF02_AG, indicating locally evolving sub-epidemics. The lack of well-defined phylogenetic structure was observed for sub-subtype A6. The estimated origin date of CRF02_AG was January 1997; CRF63_02A, April 2004; and A6, June 1995. A rapid evolutionary dynamic of CRF02_AG and A6 among Kyrgyz population since the mid-1990s was observed. We observed the high levels of HIV-1 genetic diversity and drug resistance in the study population. Complex patterns of HIV-1 phylogenetics in Kyrgyzstan were found. This study highlights the importance of molecular–epidemiological analysis for HIV-1 surveillance and treatment implementation to reduce new HIV-1 infections.